Características reprodutivas sazonais da égua crioula em uma propriedade à latitude 29º38 S no Rio Grande do Sul - Winter, Gustavo Henrique Zimmermann (2007)
The Criollo Horse breed is gaining increasing importance in our state, due to competition to economic and cultural aspects. However, few studies were developed with this horse breed. Under seasonal and natural photoperiod influence, in a stud farm at 29º38 South latitude, the length of gestation, foal s heat occurrence and duration of partum to ovulation interval, fall transition, anestrous, vernal transition and estrous were evaluated in 82 Criollo mares, with age between three and 28 years. Palpation per rectum and ultrasonography were performed daily from the beginning of the breeding season in September/2005 until December/2006. The mean and standard deviation (±SD) of gestation length in 70 mares was 335.6±10.5 days, varying from 312 to 364 days. The mean interval from parturition to first ovulation (±SD) of 42 mares that foaled between September and December of 2005 and 2006 was 20.0±14.0 days. The longer period was 71 days. A foal heat ovulation shorter then 20 days was shown on 83.3% (35/42) of the mares and, on them the mean parturition to ovulation interval (±SD) was 14.2±3.0 days. The results of estrus evaluation, during the six days prior to ovulation, showed a daily enlargement of follicle diameter of about three millimeters. The mean diameter varied from 30.1mm at the 6th day pre-ovulation to 45.6mm on the day before corpus luteum detection. The vernal transition was evaluated in 14 mares in two consecutive years. On them, 64.3% finished their transitional period between the second half of September and the first fortnight of October, close to the spring equinox. The fall transition started on May and 75% (6/8) of the mares entered the anestrous period at the second half of that month